Comparative Study of Cord Lipid Profile in Small for Gestational Age and Appropriate for Gestational Age Newborn - Sunita Arora; Shifali Gupta; Pushpjeet Sheemar (Mashhad University of Medical Sciences, 2017)
Background: This study was conducted to compare the cord blood lipid profile in term small for gestation (SGA) and appropriate for gestational age (AGA) babies as determination of cord blood lipid profile is useful screening tool for early detection of babies at higher risk as atherosclerosis has its genesis in childhood. Methods: Study Design: Hospital based cross sectional study. Setting: neonatal unit of tertiary care hospital. Subjects: 200 full term babies born at SGRDIMSR during study period out of which 100 were AGA and 100 were SGA babies. Mean cord cholesterol, triglyceride, HDL, LDL, VLDL was measured in both the groups. Results: Mean cord blood cholesterol was 72.29± 21.13 mg/dL, triglycerides 67.18± 20.36 mg/dL, HDL 28.51± 5.68 mg/dL, LDL 34.94± 16.45 mg/dL, VLDL 13.43± 04.10 mg/dl in 100 AGA babies. In 100 SGA babies, mean total cholesterol was 100.85± 26.82 mg/dl, triglycerides 82±22.58 mg/dL, HDL 27.70± 7.79 mg/dL, LDL 44.93± 7.663 mg/dL, VLDL 16.40± 4.479 mg/dL. Conclusion: Lipid profile values except HDL were significantly higher in SGA compared to AGA neonates (p